Letter from Jane Tolmach - Jane Tolmach:::::: (1970)
In this October 29, 1970 letter, Jane Tolmach of the Democratic State Central Committee's Women's Division informs Democratic nominees about the upcoming Key Women Award party held after the General Election. Each candidate is invited to recommend women volunteers to receive a gold key pin in recognition of their campaign work. The event is planned for early December or January, and nominees will be asked after the election to submit names and addresses of those they wish to honor.